2017
DOI: 10.3390/w9090652
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Patterns of the 2010–2015 Extreme Hydrological Drought across the Central Andes, Argentina

Abstract: During the period 2010-2015, the semi-arid Central Andes in Argentina (CAA) experienced one of the most severe and long-lasting hydrological droughts on record. Since the snowmelt is the most important source of water, the reduced snowfall over the mountains propagated the drought signal through the streamflows in the adjacent foothills east of the Andes ranges. Motivated by the widespread impacts on the socio-economic activities in the region, this study aims to characterize the recent hydrological drought in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 42 publications
2
55
0
7
Order By: Relevance
“…2c and 5a), emphasizing the close relationship between these two variables. The SWE decrease during the MD also extended eastward of the continental divide, thus affecting the water resources of the agricultural region in westernmost Argentina (Bianchi et al, 2016;Rivera et al, 2017). Given that the accumulation and melt of the snowpack occurs within the hydrological year, we did not find any cumulative effect of the megadrought in the SWE along the Andes of central Chile.…”
Section: Seasonal Snowpackmentioning
confidence: 71%
See 2 more Smart Citations
“…2c and 5a), emphasizing the close relationship between these two variables. The SWE decrease during the MD also extended eastward of the continental divide, thus affecting the water resources of the agricultural region in westernmost Argentina (Bianchi et al, 2016;Rivera et al, 2017). Given that the accumulation and melt of the snowpack occurs within the hydrological year, we did not find any cumulative effect of the megadrought in the SWE along the Andes of central Chile.…”
Section: Seasonal Snowpackmentioning
confidence: 71%
“…Between 2010 and 2015 the Chilean national authorities decreed emergency conditions in 7 (out of 15) administrative regions, applying exceptional water-management measures and sending relief packages to local communities (CR2, 2015). By depleting the subtropical Andes snowpack, this drought also reduced water resources in western Argentina (Bianchi et al, 2016;Rivera et al, 2017).…”
Section: Megadrought In Central Chilementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed a strong negative trend in GRACE mascon solutions in the Colorado basin (e.g. Scanlon et al, 2016) that can be associated to a decrease in snow water equivalent over the dry Central Andes (Rivera et al, 2017). Moreover, negative variations in glacier mass have been reported in southern Argentina/Chile over the Patagonia 25…”
Section: Terrestrial Water Storage (Tws)mentioning
confidence: 95%
“…Hydrol For example, a poor correlation (r < 0.2) is observed in a semiarid region covered by the Colorado basin, where snow/glacier melt has a large contribution to total runoff and corresponds to the main source of water for human activities (Rivera et al, 2017). Other locations with lower performance (NSE < 0.2) usually refer to regions strongly influenced by orography (around Andes Cordillera), which are expected due to larger uncertainties of satellite-derived precipitation in these areas (Tian and Peters-Lidard, 2010;Paiva et al, 2013).…”
Section: River Dischargesmentioning
confidence: 99%